PENGARUH EMPLOYEE ENGAGEMENT DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN KPP PRATAMA JOMBANG - Akhmad Taqiyuddin; Lailatus Sa’adah; Nanik3 Lailatul Mukarromah (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this study was to determine the effect of employee engagement and organizational culture on employee performance at KPP Pratama Jombang. The method used in this study is a quantitative method. The population in this study amounted to 81 employees while the sample amounted to 67 respondents using a purposive sampling technique. Data was collected by the questionnaire method, which was then analyzed using multiple regression analysis using SPSS version 26. The results showed that partially employee engagement variables did not exist. influence on employee performance, while the organizational culture variable influences employee performance. Simultaneously, employee engagement and organizational culture variables have a positive effect on employee performance at KPP Pratama Jombang. The results of the analysis of the coefficient of determination obtained 0.543 or 54.3%, which means that the contribution of employee engagement and organizational culture variables to employee performance is 54.3%, while the rest is influenced by other factors outside this regression model